Determination of some blood parameters during pregnancy and lactation periods in healthy akkaraman kangal ewes - Nazli Ercan; Mustafa Kockaya; Yusuf Ziya Ograk (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study to investigate the influence in reproductive status on the serum concentration of biochemical markers and some macro elements in sera of Akkaraman Kangal ewes during late pregnancy and early lactation. Materials and Methods: Twelve Akkaraman Kangal ewes were included in this study. The sheep were raised under pasture conditions and without any dietary complementation. Samples were taken during late pregnancy and early lactation from each ewe. Serum concentrations of glucose, cholesterol, creatinine, triglyceride, alkaline phosphates, total protein, albumin, very low density lipoprotein, blood urea nitrogen, calcium, phosphorus and magnesium were determined with analyzer. Results: In the ewes during lactation, the concentrations of alkaline phosphates, albumin and calcium were significantly higher (P<0.05) compared to the pregnant ewes. Conclusions: The study showed that increased alkaline phosphates, albumin and calcium levels may be induced mobilization of body reserves because of increasing milk synthesis in ewes during early lactation period and also without any dietary complementation. It will be helpful in nutritional supplements in ewes fed on pasture conditions during pregnancy and lactation periods.